Are natural resources abundance and human development a solution for environmental pressure? Evidence from top ten countries with the largest ecological footprint. (March 2021) - Pata, Ugur Korkut; Aydin, Mucahit; Haouas, Ilham
Abstract: The aim of this study is to analyze the role of globalization, renewable energy consumption, natural resources abundance, and human development index on environmental degradation for the top ten countries with the largest ecological footprint. To this end, the study employs a panel cointegration test and augmented mean group estimator. These methods are robust to cross-sectional dependence. Based on the yearly data from 1992 to 2016, the Lagrange multiplier bootstrap cointegration test results show that the analyzed variables are cointegrated. However, the empirical findings demonstrate that the human capital Kuznets curve hypothesis is not valid for the top ten countries as the sign of coefficients on the human development index and its square are negative. The panel estimator outcomes indicate that the increase in human development and renewable energy consumption has a negative and statistically significant effect on the ecological footprint. On the contrary, natural resources abundance reduces environmental quality, while globalization does not affect environmental pressure. In light of the outcomes, we can state that human development and renewable energy consumption are two essential factors in the fight against environmental pollution; however, the abundance of natural resources significantly damages the environment, so caution should be exercised in the use of natural resources. Graphical abstract: Image 1 Highlights: Investigates the validity of the human capital Kuznets curve. Cross-sectional dependence exists in the data set for all variables. Human development and renewable energy improve environmental quality. Natural resource abundance increases environmental pressure.